Fe/Ni bi-metallic organic framework supported 1T/2H MoS2 heterostructures as efficient bifunctional electrocatalysts for hydrogen and oxygen evolution. (1st May 2023) - Lin, Zhiying; Feng, Tao; Ma, Xin; Liu, Gang
Graphical abstract: Highlights: Bi-metallic MOF supported 1 T/2H MoS2 heterostructures were in-situ synthesized. The heterostructures show flower-like morphology with rich 1T MoS2 content. MoS2 @Fe/Ni-MOF600 -3 shows optimal electrocatalytic performance. Low overpotential and large ECSA are achieved for HER and OER. Abstract: Due to the high electrical conductivity and abundant active sites, 1T MoS2 shows distinguished electrocatalytic activity in hydrogen evolution reaction (HER). However, 1T MoS2 is metastable and shows low activity toward oxygen evolution reaction (OER), preventing its wide application as bifunctional electrocatalyst. Herein, we demonstrate the preparation of 1T-rich MoS2 composite catalysts for enhanced HER and OER in alkaline condition. The preparation process includes hydrothermal synthesis of Fe/Ni bi-metallic organic framework (b-MOF) and subsequent in-situ fabrication of 1T/2H MoS2 . The as-prepared composite MoS2 @Fe/Ni-MOF600 -x (x = 1, 2, 3) exhibits excellent electrocatalytic performance due to the specific nanoflower 3D structure, electron modulation effect of Fe/Ni, and high content of 1T MoS2 . Typically, MoS2 @Fe/Ni-MOF600 -3 with a relatively high Fe/Ni-MOF600 feeding showed the best catalytic performance, including low overpotential of 140 and 340 mV (to achieve a current density of 10 mA·cm −2 ) and large electrochemically active surface area (ECSA) of 1312.5 and 912.5 cm 2 for HER and OER, respectively. The study provides a novel strategy for the preparation of 1T-rich MoS2 composite catalyst for highly efficient hydrogen evolution and oxygen evolution.